Pharmaco-fUS for Characterizing Drugs for Alzheimer’s Disease – The Case of THN201, a Drug Combination of Donepezil Plus Mefloquine - Vidal, Benjamin; Droguerre, Marine; Valdebenito, Marco; Zimmer, Luc; Hamon, Michel; Mouthon, Franck; Charvériat, Mathieu (Frontiers in Neuroscience, 2020)
Donepezil (DPZ) is a potent acetylcholinesterase inhibitor, largely used worldwide to alleviate cognitive symptoms in Alzheimer’s disease (AD). Beyond the widely described neuronal impact of donepezil, it was recently shown that targeting the proteins involved in astrocyte network organization might potentiate donepezil efficacy profile using behavioral tests in AD rodent models. The present study provides new perspectives, both (i) through the use of pharmaco-fUS, a new non-clinical imaging modality to move forwards drug discovery in AD and (ii) by the profiling of two drugs on brain dynamics, one used in AD – donepezil – and the other in development – donepezil combined with mefloquine as a modulator of astrocyte network in THN201 combination.